Preparation method of glucose biosensor based on 3-mercapto-1-sodium propanesulfonate / titanium dioxide composite material

By using sodium 3-mercapto-1-propanesulfonate/titanium dioxide composite and chitosan modification on a gold electrode to immobilize glucose oxidase and catalase, the problem of insufficient detection sensitivity and current response of existing glucose biosensors is solved. problem, achieving high-precision glucose concentration detection.

CN119355085AInactive Publication Date: 2025-01-24QILU SCHOOL OF MEDICINE
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411923848.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing glucose biosensors have shortcomings in detection sensitivity and current response, which is difficult to meet the demand for high-precision detection of glucose concentration.

Method used

The golden electrode is modified by 3-cymbal-1-sodium beopine/titanium dioxide composite material, and combined with chitosan to fix glucose oxidase and peroxide enzymes to improve the sensitivity and current response of the electrode through self-assembly technology and dripping method.

Benefits of technology

It significantly improves the detection sensitivity and current response of glucose biosensor. It can show a good linear relationship within the glucose concentration range of 1-13 mmol/L, and has good anti-interference ability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355085A_ABST
    Figure CN119355085A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biochemical electrodes, and particularly relates to a preparation method of a glucose biosensor based on a 3-mercapto-1-sodium propanesulfonate / titanium dioxide composite material. The preparation method comprises the following steps: adding a nano TiO2 solution into a sodium 3-sulfydryl-1-propanesulfonate mixed solution, mixing, centrifuging, cleaning the obtained solid, and dispersing into water to obtain a sodium 3-sulfydryl-1-propanesulfonate / titanium dioxide modified solution; dispensing the 3-sulfydryl-1-sodium propanesulfonate / titanium dioxide modified liquid on the surface of a bare gold electrode, naturally airing and storing to obtain a 3-sulfydryl-1-sodium propanesulfonate / titanium dioxide modified electrode; and dispensing a cross-linking agent solution on the surface of the 3-sulfydryl-1-sodium propanesulfonate / titanium dioxide modified electrode, and airing to obtain the glucose biosensor based on the 3-sulfydryl-1-sodium propanesulfonate / titanium dioxide composite material. The sensitivity of the electrode can be improved, and the current response of the electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biochemical electrodes, and in particular relates to a method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material. Background Art

[0002] Diabetes is a disease with great hazards and many complications. When the symptoms are severe, it can also induce acute metabolic disorders, complicated by hyperosmolar hyperglycemic syndrome and diabetic ketoacidosis, endangering the life and health of patients. Due to the increase in blood sugar and fat metabolism disorders, diabetic patients are often accompanied by abnormal blood lipids. Elevated blood lipids are most likely to cause atherosclerosis and damage to the skeletal central nervous system. Diabetic patients are often accompanied by increased urine sugar concentrations, and detecting the concentration of glucose in urine is of certain significance. A positive urine sugar result is an important basis for diagnosing diabetes.

[0003] At present, the commonly used methods for measuring glucose content are: polarimetry, 3,5-dinitrosalicylic acid method (DNS method), pre-column derivatization liquid chromatography (ultraviolet detector), iodine titration and biosensor method, etc. With the continuous development of biological immobilization technology, various new types of bioelectrode sensors have been produced. The biosensor method is easy to operate, has high measurement accuracy, good specificity, and strong anti-interference ability, which can meet the requirements of the standard substance determination method.

[0004] Electrochemical biosensors are biosensors that detect microorganisms by measuring electrochemical signals. This type of sensor uses biosensitive materials (such as antibodies, enzymes, etc.) as recognition elements to specifically identify the analyte, and uses electrodes as conversion elements to convert physical or chemical signals into electrical signals. The signals are amplified and processed to qualitatively or quantitatively analyze the analyte. Electrochemical biosensors have been widely used because of their advantages such as good selectivity, high sensitivity, and fast detection speed.

[0005] The surfaces of metals and carbon materials have a certain surface energy. The distribution of this surface energy is uneven. There are defects on the crystal plane, such as steps, kinks, dislocations and adsorbed atoms, which make it easy for many substances in the solution to adsorb to these high-energy sites and cause pollution. At the same time, the surfaces of metals and carbon can be oxidized by chemical or electrochemical methods. The oxidation also increases the surface roughness and forms an inert layer, which greatly reduces its repeatability and stability. Pretreatment and modification of gold electrodes can improve the sensitivity, repeatability and stability of electrochemical sensors.

[0006] With the continuous progress of social science and technology, more and more modified materials are used to construct new electrochemical biosensors. Thiol groups can form a stable gold-sulfur bond with gold (Au) through polar covalent bonds. The gold-sulfur bond can directly assemble biomolecules connected to thiol groups on the surface of the gold electrode. The gold-sulfur bond makes the self-assembled monolayer (SAM) formed by sulfur compounds on the surface of the gold electrode have good stability, density and order.

[0007] Nanomaterials refer to materials with at least one dimension in the three-dimensional space at the nanometer level (usually 1-100nm). Due to their special size distribution, nanomaterials have surface effects and a series of unique mechanical, electrical, optical and catalytic properties. The use of nanomaterials to construct electrochemical biosensors has the advantages of accelerating the electron transfer rate, increasing the reversibility of the reaction of redox substances on the electrode surface, and having good catalytic properties and the ability to fix biomolecules.

[0008] Metal nanomaterials have been found to have functionalized biocompatibility, high surface reactivity, high catalytic efficiency and catalytic properties, and can also promote electron transfer and adsorption capabilities, and provide a suitable microenvironment for the immobilization of biomolecules. Therefore, nanometal oxides are gradually being used to immobilize biomolecules to construct enzyme-containing biosensors.

[0009] Chitosan (CTS) is a deacetylated product of chitin. It has excellent biodegradability, excellent film-forming property and biocompatibility. It is very suitable as a carrier for enzyme fixation and can be combined with other biomaterials by covalent cross-linking and other methods. Summary of the invention

[0010] The purpose of the present invention is to provide a method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material, which can increase the sensitivity of an electrode and improve the current response of the electrode.

[0011] The preparation method of the glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material of the present invention comprises the following steps: (1) After pretreatment of the gold electrode, a bare gold electrode is obtained; (2) Methanol and glacial acetic acid are added to sodium 3-mercapto-1-propanesulfonate to dissolve it, and then water is added to obtain a mixed solution of sodium 3-mercapto-1-propanesulfonate; nano-TiO 2 The solutions are mixed and centrifuged, and the obtained solid is washed and dispersed in water to obtain a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified solution; (3) dissolving chitosan, glucose oxidase and catalase in a phosphate buffer solution to obtain a cross-linking agent solution; (4) applying a drop of 3-mercapto-1-propanesulfonate sodium / titanium dioxide modified liquid on the surface of a bare gold electrode, drying it naturally and then storing it to obtain a 3-mercapto-1-propanesulfonate sodium / titanium dioxide modified electrode; (5) The crosslinker solution is drop-coated on the surface of the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide and allowed to dry to obtain a glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

[0012] In step (1), the gold electrode is pretreated by grinding the gold electrode with sandpaper and then using Al 2 O 3 Polishing powder is used to polish to a mirror surface, and then ultrasonic cleaning is performed after rinsing with distilled water, and then taken out and naturally dried, and ultrasonic cleaning is performed with anhydrous ethanol, and then the electrode surface is taken out and rinsed with distilled water and dried.

[0013] In step (2), the ratio of sodium 3-mercapto-1-propanesulfonate, methanol and glacial acetic acid is 0.1007-0.1027:9-9.4:0.4-0.6, wherein sodium 3-mercapto-1-propanesulfonate is measured in g, and methanol and glacial acetic acid are both measured in ml.

[0014] The concentration of sodium 3-mercapto-1-propanesulfonate in the sodium 3-mercapto-1-propanesulfonate mixed solution in step (2) is 0.01007-0.01027 g / ml.

[0015] In step (2), the mixed solution of 3-mercapto-1-propanesulfonic acid sodium and nano-TiO 2 The volume ratio of the solution is 0.9-1.1:1, nano-TiO 2 The mass concentration of the solution is 0.3-0.6%.

[0016] The mixing time in step (2) is 1.2-2.8 hours.

[0017] In step (2), the centrifugal speed is 2300-3500 rpm and the centrifugal time is 8-12 min.

[0018] In step (3), the mass ratio of chitosan, glucose oxidase and catalase is 0.1-0.11:0.0495-0.0512:0.0049-0.0051, and the concentration of glucose oxidase in the cross-linking agent solution is 4.95-5.12 g / L.

[0019] The phosphate buffer solution in step (3) is prepared by mixing disodium hydrogen phosphate solid and distilled water to obtain solution A, mixing sodium dihydrogen phosphate dihydrate solid and distilled water to obtain solution B, and then adjusting the pH of solution A and solution B to 7.2 to obtain the solution.

[0020] In step (4), the amount of 3-mercapto-1-propanesulfonic acid sodium / titanium dioxide modified solution drop coating is 3.18-4.46ul / mm 2 .

[0021] The storage time in step (4) is 2.5-3.5 hours.

[0022] The amount of crosslinker solution applied in step (5) is 6.34-9.55ul / mm 2 .

[0023] In step (5), the drying temperature is 2-6°C and the drying time is 5-7 hours.

[0024] The thiol groups in the gold electrode and 3-mercapto-1-propanesulfonate (MPS) structure form a stable Au-S bond through self-assembly, which enhances the stability of the electrode. In addition, 3-mercapto-1-propanesulfonate is easily soluble in water and has strong antioxidant properties. It can be used as an antioxidant to improve the activity of enzymes. Moreover, 3-mercapto-1-propanesulfonate has very little odor and can also play the role of a metal rust inhibitor when modified on a gold electrode.

[0025] Nano-TiO 2 Nano-TiO has the advantages of large specific surface area, high electrochemical catalytic activity, high loading capacity for enzymes and biocompatibility. 2 It can accelerate the electron transfer rate between glucose oxidase (GOD) and catalase (Catalase) and the electrode, increase the enzyme adsorption amount and stability, and improve the catalytic activity of the enzyme. Therefore, electrons can be quickly transferred between the active site of glucose oxidase and the electrode, which can improve the detection speed and sensitivity of subsequent glucose detection, and can also detect lower concentrations of glucose.

[0026] Although glucose biosensors can be constructed by directly fixing glucose oxidase and catalase on the electrode surface, the active sites of the enzymes are often deeply buried inside insulating proteins, which makes the enzyme electron transfer efficiency in the biosensor low. The present invention uses chitosan as an electron mediator to fix glucose oxidase and catalase on the electrode surface, which can significantly improve the detection sensitivity of the sensor. Chitosan is a linear polycationic polysaccharide rich in amino and hydroxyl groups, has a very high affinity for proteins, and has good biocompatibility, good adsorption, good film-forming properties, non-toxicity and biodegradability, etc., which is conducive to maintaining the biological activity of biological molecules. The electron mediator chitosan is fixed together with glucose oxidase, catalase, etc. on the electrode surface, which can improve the sensitivity of the glucose sensor in detecting glucose.

[0027] The enzyme-catalyzed hydrolysis reaction of glucose is as follows:

[0028] Glucose oxidase (GOD) contains two flavin adenine dinucleotides (FAD) as cofactors. GOD can catalyze glucose efficiently and specifically. From formulas (1) and (2), it can be seen that in the presence of catalase, glucose oxidase catalyzes the oxidation of β-D-glucose to produce β-D-gluconic acid and hydrogen peroxide, and then catalase decomposes hydrogen peroxide into water and oxygen. Formula (1) and formula (2) are added to obtain formula (3). From formula (3), it can be seen that 0.5 moles of oxygen are consumed when each mole of β-D-glucose is oxidized. The number of electrons transferred is proportional to the current size, that is, the glucose concentration is proportional to the current size, so the current size can be used to detect the glucose concentration.

[0029] The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared by the invention can detect glucose in urine.

[0030] The beneficial effects of the present invention are as follows: The present invention utilizes self-assembly technology to combine 3-mercapto-1-propanesulfonic acid sodium (MPS) and nano-TiO 2 Modified on the surface of the gold electrode, by nano-TiO 2 A highly sensitive and fast-responding glucose biosensor was prepared by immobilizing glucose oxidase (GOD) and catalase with chitosan. The gold electrode was modified by self-assembly technology and drop coating method, and the electrochemical behavior of the electrode in urine samples was studied by differential pulse voltammetry (DPV). The optimal experimental conditions were a phosphate buffer solution concentration of 0.10 mol / L, a pH of 7.20, and a pulse period of 0.5 seconds, and the electrode had the highest sensitivity. According to methodological investigations, the glucose biosensor prepared had good precision and stability, and showed a good linear relationship in the glucose concentration range of 1-13 mmol / L. The linear regression equation was I=1.7251C+0.1241, and the correlation coefficient R 2 The prepared glucose biosensor has a linear relationship between the concentration of glucose solution and the current within a certain range, and has a certain clinical application value. The present invention can promote the electron transfer of the glucose biosensor, improve the current response of the electrode, and increase the sensitivity of the electrode through the modification of 3-mercapto-1-propanesulfonic acid sodium, nano titanium dioxide, glucose oxidase and catalase. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1This is the electrochemical characterization diagram of the bare gold electrode, the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide, and the glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material in Example 1, in which a: bare gold electrode, b: electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide, c: glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

[0032] Figure 2 These are the differential pulse voltammograms of phosphate buffer solutions with different concentrations. In the figure, a: 0.10 mol / L, b: 0.15 mol / L, c: 0.20 mol / L, d: 0.05 mol / L, e: 0.25 mol / L.

[0033] Figure 3 These are the differential pulse voltammograms of phosphate buffer solutions at different pH values. In the figure, a: pH = 7.20, b: pH = 7.00, c: pH = 7.50, d: pH = 6.50, e: pH = 6.00, f: pH = 7.90, g: pH = 5.50, h: pH = 5.00, i: pH = 8.20.

[0034] Figure 4 These are the differential pulse voltammograms under different pulse periods, in the figure, a: 0.5s, b: 0.4s, c: 0.6s, d: 0.3s, e: 0.7s.

[0035] Figure 5 This is the standard curve of the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material. DETAILED DESCRIPTION

[0036] The present invention is further described below with reference to the embodiments.

[0037] Example 1 (1) Accurately weigh 0.2063 g potassium ferrocyanide and 1.8641 g potassium chloride, dissolve them in an appropriate amount of distilled water, transfer them to a 250 ml volumetric flask and dilute to the mark with distilled water to obtain 2.5 × 10 -3 mol / L potassium ferrocyanide solution (containing 0.1 mol / L KCl) was transferred into a brown reagent bottle and stored for later use; The gold electrode with a core diameter of 2 mm was polished with sandpaper and then 2 O 3 Polishing powder (diameter 0.05 μm) was used to polish to a mirror surface, and then the electrode surface was rinsed with distilled water and ultrasonically cleaned for 15 min. The electrode was taken out and naturally dried, and ultrasonically cleaned with anhydrous ethanol for 10 min. The electrode surface was taken out and rinsed with distilled water, and the electrode surface was dried to obtain a bare gold electrode. At a potential between -0.2 and 0.6 V, place the bare gold electrode at 2.5 × 10 -3 When the cyclic voltammetry (CV) method was used to scan in a mol / L potassium ferrocyanide solution (containing 0.1 mol / L potassium chloride), the potential difference of the polished bare gold electrode was within 100 mV, indicating that the bare gold electrode had been processed well.

[0038] (2) Accurately weigh 0.1007 g of sodium 3-mercapto-1-propanesulfonate, add 9.4 ml of methanol and 0.4 ml of glacial acetic acid, shake to dissolve, transfer to a 10 ml volumetric flask and dilute to the mark with distilled water to obtain a mixed solution of sodium 3-mercapto-1-propanesulfonate; take 1 ml of the mixed solution of sodium 3-mercapto-1-propanesulfonate and add 1 ml of nano-TiO 2 The solution was shaken by an ultrasonic cleaner for 2 hours, and then centrifuged at 3000 rpm for 10 min to collect the solid, which was washed three times with anhydrous methanol and dispersed in 2 ml of distilled water for later use, thereby obtaining a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified solution; (3) Accurately weigh solid sodium dihydrogen phosphate, add distilled water and stir to dissolve it, then transfer it to a 500 ml volumetric flask and shake it to make a solution A with a concentration of 0.1 mol / L; accurately weigh solid sodium dihydrogen phosphate dihydrate, add distilled water and stir to dissolve it, then transfer it to a 500 ml volumetric flask and shake it to make a solution B with a concentration of 0.1 mol / L; take 76 ml of solution A and 24 ml of solution B, mix them and stir them evenly, measure the pH value with a calibrated pH meter, and adjust the pH to 7.2 to obtain a phosphate buffer solution (PBS); Accurately weigh 0.1032 g chitosan, 0.0512 g glucose oxidase and 0.0049 g catalase and dissolve them in an appropriate amount of phosphate buffer solution (pH = 7.2). Use phosphate buffer solution (pH = 7.2) to make up to 10 ml in a volumetric flask to obtain a crosslinker solution, which is stored in a refrigerator (4°C). (4) Take a drop of 3-mercapto-1-propanesulfonic acid sodium / titanium dioxide modified solution and apply it on the surface of the bare gold electrode. The amount of drop is 3.18ul / mm 2 , and then stored for 3 hours after natural drying to obtain a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified electrode; (5) The crosslinker solution was drop-coated on the surface of the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide at a drop-coating volume of 6.34 ul / mm 2 , and dried at 4°C for 6 hours to obtain a glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

[0039] 1. Screening of experimental conditions: 1. Characterization of electrodes This experiment adopted a three-electrode system, with the bare gold electrode, the sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified electrode and the glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material in Example 1 as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode. -3 Cyclic voltammetry (CV) scanning was performed in a 10 mol / L potassium ferrocyanide solution (containing 0.10 mol / L KCl) at a potential between -0.2 and 0.6 V to characterize the bare gold electrode, the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide, and the glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material. The results are shown in Figure 1 .Depend on Figure 1 It can be seen that the peak current of curve c is the largest, which shows that chitosan fixes glucose oxidase and catalase on the electrode surface, promotes the ability of electron transfer, and improves the electrode sensitivity, indicating that the glucose biosensor has been prepared.

[0040] 2. Selection of different concentrations of phosphate buffered saline (PBS) Phosphate buffer solutions (pH 6.00) with concentrations of 0.05mol / L, 0.10mol / L, 0.15mol / L, 0.20mol / L, and 0.25mol / L were selected as solvents, and five portions of 0.1585g of glucose were accurately weighed as solutes, dissolved, transferred to a 100ml volumetric flask, and diluted to the mark to prepare five portions of glucose solutions with a pH of 6.00 and a concentration of 8mmol / L (the concentrations of the phosphate buffer solutions were 0.05mol / L, 0.10mol / L, 0.15mol / L, 0.20mol / L, and 0.25mol / L, respectively). The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was placed in the glucose solution, and differential pulse voltammetry scanning was performed at a pulse period of 0.5s and a potential interval of -0.2-0.6V. The results are shown in Table 1. Figure 2 .Depend on Figure 2 It can be seen that the current response value of the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material reaches the maximum in 0.10mol / L phosphate buffer solution. When the concentration of the phosphate buffer solution (pH 6.00) is greater than 0.10mol / L, as the concentration of the phosphate buffer solution (pH 6.00) gradually increases, the current response value gradually decreases, and the electrode sensitivity decreases. It can be seen that in 0.10mol / L phosphate buffer solution, the current response is the strongest, the electrode sensitivity is the highest, and the optimal phosphate buffer solution concentration is 0.10mol / L.

[0041] 3. Selection of pH of phosphate buffer solution (PBS) Under the condition of the best phosphate buffer solution concentration (0.10 mol / L), the pH of the phosphate buffer solution was investigated, and phosphate buffer solutions (concentration of 0.10 mol / L) with pH values ​​of 5.00, 5.50, 6.00, 6.50, 7.00, 7.20, 7.50, 7.90, and 8.20 were selected as solvents. Nine portions of 0.0793 g of glucose were accurately weighed as solutes, dissolved, transferred to a 50 ml volumetric flask, and diluted to the mark to prepare an 8 mmol / L glucose solution. The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was placed in the glucose solution, and detected by differential pulse voltammetry at a pulse period of 0.5 s and a potential interval of -0.2-0.6 V. The results are shown in FIG. Figure 3 .Depend on Figure 3 It can be seen that the current response value is the largest in the phosphate buffer solution with a pH of 7.20 and a concentration of 0.10 mol / L, so the optimal buffer solution pH is 7.20.

[0042] 4. Selection of pulse period Under the conditions of the optimal phosphate buffer solution concentration (0.10 mol / L) and the optimal phosphate buffer solution pH = 7.20, the characterization of differential pulse voltammetry was investigated when the pulse periods were 0.3s, 0.4s, 0.5s, 0.6s, and 0.7s, respectively. The results are shown in Figure 4 .Depend on Figure 4 It can be seen that with the increase of pulse period, the current response value of the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material also gradually increases. When the pulse period is 0.5s, the current response value reaches the maximum. When the pulse period continues to increase to 0.6s and 0.7s, the current response value gradually decreases and the sensitivity decreases. Therefore, under the conditions of the optimal phosphate buffer solution concentration (0.10mol / L) and the optimal phosphate buffer solution pH of 7.20, the optimal pulse period is 0.5s.

[0043] 2. Methodological Investigation 1. Drawing of standard curve Accurately weigh 0.0050g, 0.0149g, 0.0248g, 0.0347g, 0.0446g, 0.0545g, and 0.0648g of glucose, respectively, dissolve them with appropriate amount of 0.10mol / L phosphate buffer solution, pH 7.20, and transfer them to 25ml volumetric flasks to obtain glucose solutions with concentrations of 1.00mmol / L, 3.00mmol / L, 5.00mmol / L, 7.00mmol / L, 9.00mmol / L, 11mmol / L, and 13mmol / L, respectively. A three-electrode system was adopted, with the glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode. The currents of the glucose solutions of different concentrations were detected by an electrochemical workstation. The currents in the glucose solutions with concentrations of 1.00 mmol / L, 3.00 mmol / L, 5.00 mmol / L, 7.00 mmol / L, 9.00 mmol / L, 11 mmol / L, and 13 mmol / L were 1.3927 μA, 5.2707 μA, 9.3563 μA, 12.2684 μA, 16.3342 μA, 19.0280 μA, and 22.0181 μA, respectively. A standard curve was drawn with the glucose concentration (mmol / L) as the abscissa and the current (μA) of the glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material as the ordinate. Figure 5 As shown, the linear regression equation is I=1.7251C+0.1241, and the correlation coefficient R 2 It is 0.9967, from which it can be concluded that when the glucose concentration is in the range of 1-13 mmol / L, as the glucose concentration increases, the current also increases, and the current intensity has a good linear relationship with the glucose concentration.

[0044] 2. Determination of precision The glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was used to continuously measure a glucose solution with a concentration of 5.00 mmol / L 5 times, and the current values ​​obtained were 9.2313 μA, 9.1198 μA, 9.3183 μA, 9.2422 μA, and 9.1851 μA, respectively. From the above data, it can be measured that the relative standard deviation (RSD) value is 0.796%, and the glucose biosensor has good precision.

[0045] 3. Determination of stability Take the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1, and detect a glucose solution with a concentration of 5.00 mmol / L under the conditions of optimal phosphate buffer solution concentration (0.1 mol / L) and optimal buffer solution pH (pH = 7.20). The current value is measured at different times of 1h, 4h, 12h, 24h, 30h, and 36h. The measured current values ​​are 9.0745μA, 9.0519μA, 9.0111μA, 8.9703μA, 8.8889μA, and 8.8208μA, respectively. After calculation, the relative standard deviation (RSD) value is 1.09%, and the glucose biosensor has good stability within 36 hours.

[0046] 4. Anti-interference detection When detecting glucose in urine, substances such as ascorbic acid, urea and inorganic salts contained in urine may interfere with the detection. Therefore, ascorbic acid, urea, potassium salt and sodium salt are set as interference reagents to detect whether they will affect the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

[0047] 0.0149 g potassium chloride and 0.0495 g glucose were accurately weighed, dissolved in a phosphate buffer solution with a concentration of 0.10 mol / L and a pH of 7.20, transferred to a 50 ml volumetric flask and diluted to the scale to prepare a 5.00 mmol / L glucose solution (containing 4.00 mmol / L potassium chloride solution). The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was used for detection. At a potential between -0.2 and 0.6 V and a pulse period of 0.5 s, the detection result was 9.1198 μA, which was similar to the detection current of 9.0655 μA without adding potassium chloride, indicating that potassium chloride had no interference with the detection of glucose.

[0048] 0.0117 g of sodium chloride and 0.0499 g of glucose were accurately weighed, dissolved in a phosphate buffer solution with a concentration of 0.10 mol / L and a pH of 7.20, and transferred to a 50 ml volumetric flask to make a 5.00 mmol / L glucose solution (containing 4.00 mmol / L sodium chloride solution). The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was used for detection. The detection result was 9.1063 μA, which was similar to the detection current of 9.0655 μA without adding potassium chloride, indicating that sodium chloride had no interference with the detection of glucose.

[0049] 0.0350 g of L-ascorbic acid and 0.0502 g of glucose were accurately weighed, dissolved in a phosphate buffer solution with a concentration of 0.10 mol / L and a pH of 7.20, and transferred to a 50 mL volumetric flask to make up to volume to obtain a 5.00 mmol / L glucose solution (containing 4.00 mmol / L L-ascorbic acid solution). The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was used for detection. The detection result was 9.0383 μA, which was similar to the detection current of 9.0655 μA without adding L-ascorbic acid, indicating that L-ascorbic acid had no interference with the detection of glucose.

[0050] 0.0122 g urea and 0.0491 g glucose were accurately weighed, dissolved in 0.10 mol / L phosphate buffer solution with a pH of 7.20, and transferred to a 50 ml volumetric flask to obtain a 5.00 mmol / L glucose solution (containing 4.00 mmol / L urea solution). The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was used for detection, and the detection result was 9.0313 μA, which was similar to the detection current of 9.0655 μA without adding urea, indicating that urea had no interference with the detection of glucose.

[0051] 5. Recovery test 100 ml of urine from a diabetic patient was taken, and the pH was adjusted to 7.20 with 0.10 mol / L phosphate buffer solution to obtain a urine sample. 10.25 ml of the urine sample was placed in a 100 ml volumetric flask, and phosphate buffer solution with pH = 7.20 was added to the scale to serve as a blank solution. 10.25 ml of the blank solution was taken and measured using the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 under optimal conditions, and its current value I was measured. 1 is 4.7978μA, and the concentration is calculated as C 1 , calculate the mass m of glucose it contains 1 0.0050g. Take 10.25ml of blank solution and place it in a 100ml volumetric flask. Repeat six times and accurately weigh the mass m 2 Two portions of glucose, 0.0040g, 0.0050g, and 0.0060g (equivalent to m 1 80%, 100%, 120%), the weighed mass m 2The glucose was added to a 100 ml volumetric flask containing 10.25 ml of blank solution, and the volume was fixed to the scale line with 0.10 mol / L, pH=7.20 phosphate buffer solution to obtain the test sample; the glucose biosensor based on 3-mercapto-1-propanesulfonic acid sodium / titanium dioxide composite material prepared in Example 1 was used to measure the test sample, and the average value was taken after three consecutive measurements to obtain the average current value I, which was substituted into the linear regression equation to calculate the concentration, and then the mass of glucose contained in the test sample was calculated as m 3 , into the formula The sample recovery rate was calculated, where P is the sample recovery rate. The sample recovery test results are shown in Table 1.

[0052]

[0053] 6. Detection of glucose concentration in urine The urine sample was adjusted to pH 7.20 with 0.10 mol / L phosphate buffer solution, and then the current was detected using the glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1. The current was substituted into the linear regression equation I=1.7251C+0.1241 in the standard curve to calculate the glucose concentration contained therein and compare it with the test results of the hospital laboratory.

[0054] The glucose concentration in urine samples from the hospital laboratory mainly ranged from 2.50 to 5.50 mmol / L, all within the standard curve range. The glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material prepared in Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum electrode was used as the auxiliary electrode. Differential pulse voltammetry scanning was performed at a potential between -0.2 and 0.6 V in the test solution. In urine containing 3.00mmol / L glucose (hospital result), the currents measured after three consecutive scans were 5.2599μA, 5.2327μA and 5.2055μA respectively, and the average current was 5.2327μA. The calculated concentration was about 2.96mmol / L. The test results of the prepared glucose biosensor in urine containing 3mmol / L glucose were basically consistent with the results of the hospital laboratory; in urine containing 5mmol / L glucose (hospital result), the currents measured after three scans were 9.0519μA, 8.9649μA and 9.0763μA, and the average current was 9.0310μA. The calculated concentration was about 5.16mmol / L. The test results of the prepared glucose biosensor in urine containing 5mmol / L glucose were basically consistent with the results of the hospital laboratory. Therefore, the glucose biosensor has certain clinical use value.

[0055] Example 2 (1) 2.5 × 10-3 The preparation method of mol / L potassium ferrocyanide solution (containing 0.1 mol / L KCl) is the same as that in Example 1; The gold electrode with a core diameter of 2 mm was polished with sandpaper and then 2 O 3 Polishing powder (diameter 0.05 μm) was used to polish to a mirror surface, and then the electrode surface was rinsed with distilled water and ultrasonically cleaned for 15 min. The electrode was taken out and naturally dried, and ultrasonically cleaned with anhydrous ethanol for 10 min. The electrode surface was taken out and rinsed with distilled water, and the electrode surface was dried to obtain a bare gold electrode. At a potential between -0.2 and 0.6 V, place the bare gold electrode at 2.5 × 10 -3 When the cyclic voltammetry (CV) method was used to scan in a mol / L potassium ferrocyanide solution (containing 0.1 mol / L potassium chloride), the potential difference of the polished bare gold electrode was within 100 mV, indicating that the bare gold electrode had been processed well.

[0056] (2) Accurately weigh 0.1027 g of sodium 3-mercapto-1-propanesulfonate, add 9 ml of methanol and 0.6 ml of glacial acetic acid, shake to dissolve, transfer to a 10 ml volumetric flask and dilute to the mark with distilled water to obtain a mixed solution of sodium 3-mercapto-1-propanesulfonate; take 1.1 ml of the mixed solution of sodium 3-mercapto-1-propanesulfonate and add 1 ml of nano-TiO 2 The solution was shaken by an ultrasonic cleaner for 1.2 hours, and then centrifuged at 2300 rpm for 12 minutes to collect the solid, and washed three times with anhydrous methanol, and dispersed in 2 ml of distilled water for standby use, thus obtaining a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified solution; (3) The preparation method of phosphate buffer solution is the same as that of Example 1; Accurately weigh 0.1 g chitosan, 0.0495 g glucose oxidase and 0.005 g catalase and dissolve them in an appropriate amount of phosphate buffer solution (pH = 7.2). Use phosphate buffer solution (pH = 7.2) to make up to 10 ml in a volumetric flask to obtain a crosslinker solution, which is stored in a refrigerator (4°C). (4) Take a drop of 3-mercapto-1-propanesulfonic acid sodium / titanium dioxide modified solution and apply it on the surface of the bare gold electrode. The amount of drop is 4.46ul / mm 2 , and then stored for 2.5 hours after natural drying to obtain a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified electrode; (5) The crosslinker solution was drop-coated on the surface of the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide at a drop-coating volume of 9.55 ul / mm 2 , and dried at 2°C for 7 hours to obtain a glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

[0057] Example 3 (1) 2.5 × 10 -3 The preparation method of mol / L potassium ferrocyanide solution (containing 0.1 mol / L KCl) is the same as that in Example 1; The gold electrode with a core diameter of 2 mm was polished with sandpaper and then 2 O 3 Polishing powder (diameter 0.05 μm) was used to polish to a mirror surface, and then the electrode surface was rinsed with distilled water and ultrasonically cleaned for 15 min. The electrode was taken out and naturally dried, and ultrasonically cleaned with anhydrous ethanol for 10 min. The electrode surface was taken out and rinsed with distilled water, and the electrode surface was dried to obtain a bare gold electrode. At a potential between -0.2 and 0.6 V, place the bare gold electrode at 2.5 × 10 -3 When the cyclic voltammetry (CV) method was used to scan in a mol / L potassium ferrocyanide solution (containing 0.1 mol / L potassium chloride), the potential difference of the polished bare gold electrode was within 100 mV, indicating that the bare gold electrode had been processed well.

[0058] (2) Accurately weigh 0.102 g of sodium 3-mercapto-1-propanesulfonate, add 9.2 ml of methanol and 0.5 ml of glacial acetic acid, shake to dissolve, transfer to a 10 ml volumetric flask and dilute to the mark with distilled water to obtain a mixed solution of sodium 3-mercapto-1-propanesulfonate; take 0.9 ml of the mixed solution of sodium 3-mercapto-1-propanesulfonate and add 1 ml of nano-TiO 2 The solution was shaken by an ultrasonic cleaner for 2.8 hours, and then centrifuged at 3500 rpm for 8 minutes to collect the solid, and washed three times with anhydrous methanol, and dispersed in 2 ml of distilled water for standby use, thus obtaining a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified solution; (3) The preparation method of phosphate buffer solution is the same as that of Example 1; Accurately weigh 0.11 g chitosan, 0.0505 g glucose oxidase and 0.0051 g catalase and dissolve them in an appropriate amount of phosphate buffer solution (pH = 7.2). Use phosphate buffer solution (pH = 7.2) to make up to 10 ml in a volumetric flask to obtain a crosslinker solution, which is stored in a refrigerator (4°C). (4) Take a drop of 3-mercapto-1-propanesulfonic acid sodium / titanium dioxide modified solution and apply it on the surface of the bare gold electrode. The amount of drop is 3.55ul / mm 2 , and then stored for 3.5 hours after natural drying to obtain a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified electrode; (5) The crosslinker solution was drop-coated on the surface of the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide at a drop-coating volume of 7.42 ul / mm 2 , and dried at 6°C for 5 hours to obtain a glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

Claims

1. A method for preparing a glucose biosensor based on sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material, characterized in that The steps include: (1) After pretreatment of the gold electrode, a bare gold electrode is obtained; (2) Methanol and glacial acetic acid are added to sodium 3-mercapto-1-propanesulfonate to dissolve it, and then water is added to obtain a sodium 3-mercapto-1-propanesulfonate mixed solution; nano-TiO2 solution is added to the sodium 3-mercapto-1-propanesulfonate mixed solution, mixed, centrifuged, and the obtained solid is washed and dispersed in water to obtain a sodium 3-mercapto-1-propanesulfonate / titanium dioxide modified solution; (3) dissolving chitosan, glucose oxidase and catalase in a phosphate buffer solution to obtain a cross-linking agent solution; (4) applying a drop of 3-mercapto-1-propanesulfonate sodium / titanium dioxide modified liquid on the surface of a bare gold electrode, drying it naturally and then storing it to obtain a 3-mercapto-1-propanesulfonate sodium / titanium dioxide modified electrode; (5) The crosslinker solution is drop-coated on the surface of the electrode modified with sodium 3-mercapto-1-propanesulfonate / titanium dioxide and allowed to dry to obtain a glucose biosensor based on the sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material.

2. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that In step (1), the gold electrode is pretreated by grinding the gold electrode with sandpaper, then polishing it to a mirror surface with Al2O3 polishing powder, rinsing it with distilled water and then ultrasonic cleaning it, taking it out to dry naturally, ultrasonic cleaning it with anhydrous ethanol, taking it out to rinse the electrode surface with distilled water, and drying it.

3. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that In step (2), the ratio of sodium 3-mercapto-1-propanesulfonate, methanol and glacial acetic acid is 0.1007-0.1027:9-9.4:0.4-0.6, wherein sodium 3-mercapto-1-propanesulfonate is measured in g, and methanol and glacial acetic acid are both measured in ml.

4. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that The concentration of sodium 3-mercapto-1-propanesulfonate in the sodium 3-mercapto-1-propanesulfonate mixed solution in step (2) is 0.01007-0.01027 g / ml.

5. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that In step (2), the volume ratio of the sodium 3-mercapto-1-propanesulfonate mixed solution to the nano-TiO2 solution is 0.9-1.1:1, and the mass concentration of the nano-TiO2 solution is 0.3-0.6%.

6. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that In step (2), the mixing time is 1.2-2.8 hours; the centrifugal speed is 2300-3500 rpm, and the centrifugal time is 8-12 minutes.

7. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that In step (3), the mass ratio of chitosan, glucose oxidase and catalase is 0.1-0.11:0.0495-0.0512:0.0049-0.0051, and the concentration of glucose oxidase in the cross-linking agent solution is 4.95-5.12 g / L.

8. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that The phosphate buffer solution in step (3) is prepared by mixing disodium hydrogen phosphate solid and distilled water to obtain solution A, mixing sodium dihydrogen phosphate dihydrate solid and distilled water to obtain solution B, and then adjusting the pH of solution A and solution B to 7.2 to obtain the solution.

9. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that The storage time in step (4) is 2.5-3.5 hours.

10. The method for preparing a glucose biosensor based on a sodium 3-mercapto-1-propanesulfonate / titanium dioxide composite material according to claim 1, characterized in that In step (5), the drying temperature is 2-6°C and the drying time is 5-7 hours.

Citation Information

Patent Citations

  • Electrode modified by chloride, oxide enzyme capable of catalyzing organic reaction in high effect

    CN101004404A

  • Method for manufacturing an electrochemical-based analytical test strip with hydrophilicity enhanced metal electrodes

    CN101063679A

  • Method for preparing fixed enzyme electrode by using TiO2 as carrier

    CN101813660A

  • Preparation method of double-enzyme glucose sensor based on graphene

    CN103033549A

  • Method for using 2, 3-sodium dimercaptosulphonate simultaneously as stabilizer and sulfur source for preparation of CdTe / CdS quantum dots

    CN106244146A